The Diversity of Anuran Species in the Talago Waterfall, Tanjung Raya, Agam, West Sumatera - Wulandari Wulandari; Fitra Arya Dwi Nugraha; Rijal Satria; Yusni Atifah (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Changing the function of habitat into a tourism area will have an impact on the diversity of Anuran species. This condition is currently happening in the Talago Nagari Paninjauan Waterfall Area, Tanjung Raya District, Agam Regency, West Sumatra. This study is therefore important for revealing the diversity of Anuran species before the impact to this habitat increase in the future. This study used the VES (Visual Encounter Survey) sampling technique, and information on various localities and the microhabitat of each species was recorded. A total 48 individuals, with 12 species belonging to six families of Anuran was collected. Species diversity in the Talago Waterfall area shows a medium level of diversity, with an index of 2.2653, a medium species richness index of 2.8414. In this area, no dominant species were found with a low dominance index (0.1207). If the level of tourism activity in the Talago Waterfall area increases, it will have an effect in the future by causing habitat disruption and the presence of Anura; thus, related parties must be able to take appropriate action on tourism activities in the area.